The Effect of Student’s Intelligence in Writing Narrative Text at Grade X of SMA Methodist Berastagi - Marisa Yunita Br Depari (Formosa Journal of Sustainable Research, 2023)
The student aims at examining (1) the level of linguistics intelligence of grade X students at SMA Methodist Berastagi, (2) writing narrative text skills of grade X students at SMA Methodist Berastagi, and (3) whether there is significant influence of linguistics intelligence in writing narrative text of grade X students at SMA Methodist Berastagi. The type of this study was quantitative. Data were collected by Pre-test and Post-test. The result of the study reveal that: The average score obtained by grade X students at SMA Methodist Berastagi based on The Result The Pre-Test score for the Experimental Group was 57,8, with a maximum of 75 and a minimum of 33. Based on the results of the pre-test on the control group, SMA Methodist Berastagi's grade X pupils' average score was 45 was the lowest and 64,6 was the highest score. Based on the results of the post-test in the experimental group, grade X students at SMA Methodist Berastagi received an average score of 80,1; the best score was 94, and the lowest score was 71. Based on the results of the post-test in the control group, SMA Methodist Berastagi pupils in grade X received an average score of 79.2 out of 100, the highest score was 92, and the lowest score was 71